Perspektif Hukum Ekonomi Islam Tentang Pola Bagi Hasil Usaha Dalam Kerjasama Permodalan Jual-Beli Motor (Studi Kasus Di Show Room An-Najah Motor Selaawi Garut) - Gausian, Gini; Muiz, Abdul (Jurnal Hukum Ekonomi Syariah, 2023)
Profit sharing in a collaboration is a form of system that includes procedures for sharing business results between the provider of funds and the manager of funds in which an agreement or joint bond is carried out in a particular business then in a collaboration it is promised that there will be a sharing of the profits to be obtained between the two parties party or more. As for the formulation: (1) How is the practice of the profit sharing pattern in the capital cooperation in buying and selling motorbikes in the An-Najah Motor show room? (2) How, according to the view of Islamic Economic Law, when the distribution of business results is different from the agreement at the beginning of the agreement that had been determined in the buying and selling capital cooperation in the An-Najah Motor show room? The objectives are: (1) To find out how the practice of profit sharing patterns in capital cooperation is actually carried out in the An-Najah Motor show room. (2) To find out how according to Islamic Economic Law regarding the practice of profit-sharing patterns in cooperation, for capital with a different nominal amount given by each member of An-Najah Motor investors. This type of research is Field Research or field study using a qualitative approach. Based on the results of the research it is concluded that the implementation of the business profit sharing pattern in the cooperation of buying and selling capital of motorbikes in the An-Najah Motor show room fulfills the existing requirements as in terms of fulfilling the requirements in cooperate for profit sharing with contracts (musyarakah).However, in its implementation there are still gaps in the theory of Islamic Economic Law in its implementation which is less effective, namely, in terms of fulfilling contracts which are carried out only orally, and sharing of results that have not been mutually agreed upon regarding changes that are taking place , the responsibility for losses incurred jointly is still evenly distributed among members which can harm one party and there is no time limit for cooperation which can harm the manager.